1999
DOI: 10.1046/j.1365-2427.1999.00430.x
|View full text |Cite
|
Sign up to set email alerts
|

AusRivAS: using macroinvertebrates to assess ecological condition of rivers in Western Australia

Abstract: Summary 1. AusRivAS (Australian River Assessment Scheme) models were developed, using macroinvertebrates as indicators, to assess the ecological condition of rivers in Western Australia as part of an Australia‐wide program. The models were based on data from 188 minimally disturbed reference sites and are similar to RIVPACS models used in Britain. The major habitats in the rivers (macrophyte, channel) were sampled separately and macroinvertebrates collected were identified to family level. 2. Laboratory sortin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
162
0
4

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(173 citation statements)
references
References 26 publications
7
162
0
4
Order By: Relevance
“…Although we did not evaluate cost and processing times, we would expect that live-sorting would be significantly faster. Smith et al (1999) found that the cost of laboratory sorted samples was about 20% greater than that of live picking, which was 40% faster than laboratory sorting. Other benefits to the live-sort approach include a reduction in the amount of material that is returned to the lab which is beneficial for hard to reach sites (Chessman, 1995), the need for less expensive equipment and less preservatives, all which benefit community groups (Campbell, 2007).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although we did not evaluate cost and processing times, we would expect that live-sorting would be significantly faster. Smith et al (1999) found that the cost of laboratory sorted samples was about 20% greater than that of live picking, which was 40% faster than laboratory sorting. Other benefits to the live-sort approach include a reduction in the amount of material that is returned to the lab which is beneficial for hard to reach sites (Chessman, 1995), the need for less expensive equipment and less preservatives, all which benefit community groups (Campbell, 2007).…”
Section: Discussionmentioning
confidence: 96%
“…The under-representation of certain taxa in live-sorted samples has called into question the accuracy of this method and whether it can be compared with preserved and microscope-aided sorting (Smith et al, 1999;Humphrey et al, 2000;Nichols and Norris, 2006). However, the live-sort method has also been shown to collect more taxa than microscope sorting (Borisko et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Biological indicators are a wellestablished monitoring tool for estuarine and freshwater ecosystems 25,26 and also find application in coral reef ecosystems 27 systems, which has led to holistic sampling efforts to establish the first microbial baselines for soils and marine environments. We argue that the establishment and ongoing assessment of such microbial baselines will be crucial to understanding microbial dynamics in response to broad ranging anthropogenic impacts.…”
Section: Microbes As Indicators Of Coral Reef Healthmentioning
confidence: 99%
“…Macro-invertebrates have been selected as the key indicator group for assessment of the health of Australia's rivers using biological indicators under the National River Health Program (Smith et al, 1999). Macro-invertebrates are found in most habitats, generally have limited mobility, are easy to catch using standard collecting methods, and have a range of sensitivities to changes in water quality and habitats, and are thus good indicators of ecological 'health'.…”
Section: Ecological Samplingmentioning
confidence: 99%